"We Understand You Hate Us": Latinx Immigrant‐Origin Adolescents' Coping with Social Exclusion. (25th April 2022) - López Hernández, Guadalupe
Abstract : Little research has focused on how adolescents are faring with the national context of exclusion. Growing evidence suggests that exclusionary efforts signal messages of who belongs (and who does not) in the United States. This study draws from a risk and resilience model to understand how Latinx immigrant‐origin adolescents react and adapt to social exclusion. A total of 41 adolescents between the ages of 13 to 24 ( M age  = 18.85) completed a semistructured interview. Results revealed participants' use of avoidant and active coping strategies to deal with exclusion. There was a shift in coping responses across developmental stages. Future research and recommendations are provided to address systems that need to be dismantled to foster a sense of belonging for adolescents.